The SpasT-SCI-T trial protocol: Investigating calpain-mediated sodium channel fragments as biomarkers for traumatic CNS injuries and spasticity prediction. - Guillaume Baucher; Sylvie Liabeuf; Cécile Brocard; Aurélie Ponz; Karine Baumstarck; Lucas Troude; Marc Leone; Pierre-Hugues Roche; Frédéric Brocard (PLoS ONE)
Spinal cord injury and traumatic brain injury are major causes of long-term disability and are often complicated by spasticity, a motor disorder characterized by increased muscle tone and exaggerated reflexes that significantly impair quality of life. Current diagnostic methods lack the sensitivity needed to accurately predict the severity of injury or the onset and progression of spasticity. Trauma-induced calcium dysregulation activates calpains, a family of proteases that cleave sodium channels, disrupting their inactivation and increasing persistent sodium currents. This cascade drives the overexcitability of motoneurons, contributing to the development of spasticity. Consequently, sodium channel fragments have emerged as promising biomarkers that link injury mechanisms to clinical outcomes. The present SpasT-SCI-T clinical trial protocol aims to evaluate sodium channel fragments as blood biomarkers for assessing the severity of spinal cord and traumatic brain injuries, as well as their potential to predict clinical outcomes, including the development of spasticity. This prospective, multicenter, case-control and cohort study involves 40 participants: 20 individuals with spinal cord injury, 10 individuals with traumatic brain injury, and 10 healthy controls. Blood samples are collected within six hours of injury and at follow-up points over six months. Clinical outcomes, including spasticity (assessed using the Modified Ashworth Scale), neurological recovery (measured by the American Spinal Injury Association Impairment Scale and Glasgow Coma Scale), and quality of life (evaluated using the Short Form-36 Health Survey), are analyzed in correlation with biomarker levels. We anticipate that calpain-mediated sodium channel fragments will transform the management of central nervous system injuries by enabling early diagnosis, improving prognostic accuracy, and guiding personalized therapeutic strategies. The clinical trial is registered on ClinicalTrials.gov (NCT06532760, January 10, 2024), with Assistance Publique-Hôpitaux de Marseille as the sponsor.